Placenta accreta in an early pregnancy: case report - Gaviria Criollo, Camilo Andrés (2022)
First trimester placenta accreta is an uncommon event. There are few cases reported in the literature, several associated with uterine rupture and all of them with risk factors. This pathology can be life-threatening for the mother. At such an early stage of pregnancy, abnormal placentation is diagnosed mainly due to massive hemorrhage during uterine curettage. It is of extreme importance to diagnose it before delivery or uterine evacuation, to prevent associated morbidity and mortality. We present the case of a patient with placenta accreta in early pregnancy, who consulted for abnormal uterine bleeding. We describe the clinical history, imaging and management of the patient.